2013
DOI: 10.1002/star.201300014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on the physicochemical and binder properties of tigernut starch

Abstract: Tigernut starch is starch extracted from the tubers of Cyperus esculentus L. a perennial herb commonly known as tigernut. The effect of pH on the foaming, gelatinization, solubility, swelling, paste clarity, viscosity, freeze–thaw stability, and binder efficiency of the starch in buffer solutions of pHs 4, 7, and 9.2, representative of acid, neutral, and alkaline pHs were evaluated. Marked pH responsiveness was observed in all these parameters to varying degrees. The foaming capacity, paste clarity, freeze–tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 31 publications
(60 reference statements)
1
17
0
2
Order By: Relevance
“…The lowest solubility of cassava starch shown by deionized water compared to tap water and mineral water (Table 3) could be due to its lowest pH value (Table 1) that limits partial starch gelatinization, hence reduces swelling power and solubility of starch, unlike at higher pH (Adebowale and Lawal, 2005). This result opposed the finding reported by Builders et al (2014), which stated that a pH condition which is higher than 7 reduces the solubility of tiger nut starch. The highest solubility of cassava starch treated with mineral water may indicate weakest bonding forces within starch granules (Aryee et al, 2006) compared to the cassava starch samples treated with other types of water and commercial starch.…”
Section: Effect Of Different Types Of Water On Physicochemical Propermentioning
confidence: 66%
“…The lowest solubility of cassava starch shown by deionized water compared to tap water and mineral water (Table 3) could be due to its lowest pH value (Table 1) that limits partial starch gelatinization, hence reduces swelling power and solubility of starch, unlike at higher pH (Adebowale and Lawal, 2005). This result opposed the finding reported by Builders et al (2014), which stated that a pH condition which is higher than 7 reduces the solubility of tiger nut starch. The highest solubility of cassava starch treated with mineral water may indicate weakest bonding forces within starch granules (Aryee et al, 2006) compared to the cassava starch samples treated with other types of water and commercial starch.…”
Section: Effect Of Different Types Of Water On Physicochemical Propermentioning
confidence: 66%
“…The pH of the starch of sample A was 7.6, while that of sample B was 7.5 ( Table 1). The pH variation can alter the physicochemical properties of native starches and can impart new functionality (Builders et al, 2014).…”
Section: Moisture Fiber Ash Content and Phmentioning
confidence: 99%
“…On the other hand, the exposure of inner hydrophobic surface to water and dislocation of polymer chains has also been reported to occur for the effect of partial hydrolysis of starch in acidic and alkaline solutions [22]. Builders et al [23] found that the gelatinization temperature is remarkably sensitive to pH in the gelatinization of tigernut starch. In contrast, Simonin et al [24] found that pH does not have strong effect on gelatinization of waxy starches, but that pH has a small and significant (p < 0.05) effect on gelatinization of those starches under pressure.…”
Section: Discussionmentioning
confidence: 99%